Interview: AcademyHealth and the future of comparative effectiveness research: making sure evidence matters. (January 2012) - Simpson, Lisa
Dr Lisa Simpson is the president and CEO of AcademyHealth, and its advocacy arm, the Coalition for Health Services Research. A nationally recognized health policy researcher and pediatrician, Dr Simpson is a passionate advocate for the translation of research into policy and practice. Before joining AcademyHealth, Dr Simpson was director of the Child Policy Research Center at Cincinnati Children''s Hospital Medical Center and Professor of Pediatrics in the Division of Health Policy and Clinical Effectiveness, Department of Pediatrics, University of Cincinnati (OH, USA). She served as the Deputy Director of the Agency for Healthcare Research and Quality (AHRQ) from 1996 to 2002. She previously served on the Institute of Medicine''s Committee on Comparative Effectiveness Research Priorities and the Committee on Highly Effective Clinical Services. Dr Simpson is a member of the Robert Wood Johnson Clinical Scholars Program National Advisory Council and the AHRQ Healthcare Cost and Utilization Project (HCUP) Steering Committee. Dr Simpson''s research focuses on improving the performance of the healthcare system and includes studies of the quality and safety of care, the role of health information technology in improving the quality of care, health and healthcare disparities, and the health policy and system response to childhood obesity. Dr Simpson earned her undergraduate and medical degrees at Trinity College (Dublin, Ireland), a master''s in public health at the University of Hawaii (HI, USA), and completed a post-doctoral fellowship in health services research and health policy at the University of California, San Francisco (CA, USA).